2000
DOI: 10.1007/bf03020727
|View full text |Cite
|
Sign up to set email alerts
|

Patient supplemented epidural analgesia after major abdominal surgery with bupivacaine/fentanyl or ropivacaine/fentanyl

Abstract: Purpose: To compare analgesic efficacy and occurrence of motor block and other side effects during patient supplemented epidural analgesia (PSEA) with either ropivacaine/fentanyl or bupivacaine/fentanyl mixtures. Methods:In a prospective, randomized, double-blind study, 32 ASA I-III patients undergoing major abdominal surgery received an epidural catheter at the T 8 -T 10 , followed by integrated general epidural anesthesia. Postoperative epidural analgesia was provided using a patient controlled pump with eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 24 publications
2
8
0
2
Order By: Relevance
“…Berti M et al, observed higher number of incremental doses and larger total volume of analgesic solution infused over 24 hours in the 0.125% bupivacaine with 2μg/ml fentanyl group [15]. We report similar findings with higher total mean epidural consumption, total epidural boluses and total rescue analgesic consumption in Group IV of our study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Berti M et al, observed higher number of incremental doses and larger total volume of analgesic solution infused over 24 hours in the 0.125% bupivacaine with 2μg/ml fentanyl group [15]. We report similar findings with higher total mean epidural consumption, total epidural boluses and total rescue analgesic consumption in Group IV of our study.…”
Section: Discussionsupporting
confidence: 88%
“…Rapid patient mobilization is an integral part of speedy recovery after lower limb surgery, and this leads to a decrease in duration of hospitalization by one to two days [18]. Our results are simiar to those of Berti et al, as they also reported higher supplemental analgesic consumption in the patients receiving combination of 0.125 % bupivacaine and 2 μg/ml fentanyl as compared to those who received 0.2 % ropivacaine [15]. Similarly, Kanai A et al, also reported least VAS scores in patients receiving 0.2% ropivacaine with 2.2μg/ml fentanyl in their study [19].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Tem-se utilizado fentanil, ou morfina, associados aos anestésicos locais, por via peridural em dose única ou através de cateter, em doses intermitentes ou contínuas por bomba de infusão programada 8 . Estas bombas permitem o controle da analgesia pelo paciente, trazendo mais conforto e segurança, possibilitando uma maior interatividade do doente com sua recuperação [8][9][10][11][12][13][14] . Outra utilização destas bombas se faz por via venosa, porém com maior consumo de opióides 5,6 .…”
Section: Introductionunclassified
“…Epidural fentanyl or morphine associated to local anesthetics have been used in single doses or through catheter's, in intermittent boluses or continuous infusion by programmed infusion pump's 8 . These pumps allow analgesia to be patient-controlled, not only bringing more comfort and safety but also creating a higher interactivity of patients with their recovery [8][9][10][11][12][13][14] . There are pumps designed for intravenous infusion of drugs too, though its use is related to higher opioid consumption 5,6 .…”
Section: Introductionmentioning
confidence: 99%